ETNOMATEMATIKA: ETNOMODELING TARI MERAK SUNDA - Dharsono, Farhan Maulana; Supratman; Prabawati, Mega Nur (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This study aims to determine the ethnomodeling found in the Sundanese Merak dance. This type of research is qualitative research with ethnographic methods. There are three elements that are the sources of research data, namely the place and actors that occur at the PUSBITARI (Pusat Bina Tari Irawati Durban) and ISBI Bandung studios. The researcher conducted direct interviews with classical Sundanese dance maestros, dance trainers, dancers, and dance teachers. The activities carried out were conducting initial observations and direct interviews with informants. The data collection technique in this study used triangulation. The data analysis used was content analysis techniques, triangulation techniques, and finding patterns. The results of the study showed that the trainers and dancers of the Sundanese Merak dance at the PUSBITARI and ISBI Bandung studios tended to be proficient in mathematics in determining the direction of the dancers with the concept of related angles or by using time or clock benchmarks. Ethnomodeling in the Sundanese Merak dance is based on the 10 most important directions which are the concept of the relationship between the clock hands and the size of the angle. This calculation is a mathematical concept on how to calculate the size of the angle of the dancer's direction of face which is related to the direction of the clock hand and the concept of relational angle.